Volume 5: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30348
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Interaction of Labyrinth Seal Leakage Flow and Main Flow in an Axial Turbine

Abstract: This paper presents the simulation of the flow in a 1.5 stage low-speed axial turbine with shrouded rotor blades and focuses on the interaction of the labyrinth seal leakage flow with the main flow. The presented results were obtained using the Navier-Stokes code ITSM3D developed at University of Stuttgart. A comparison of the computational results with experimental data of this test case gained at Ruhr-Universita¨t Bochum verifies that the flow solver is capable of reproducing the leakage flow effects to a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Some of the earlier results have been presented in several publications, e.g. Peters et al [14], Giboni et al [15], and Anker and Mayer [16].…”
Section: Introductionmentioning
confidence: 79%
“…Some of the earlier results have been presented in several publications, e.g. Peters et al [14], Giboni et al [15], and Anker and Mayer [16].…”
Section: Introductionmentioning
confidence: 79%
“…This indicates that a more complete understanding of unsteady interaction of the leakage flow with the main flow is required. The CFD simulations of Anker & Mayer (2002) also underlined the importance of considering unsteady measurement and simulations to obtain a more realistic representation of these effects. Hunter & Manwaring (2000) and Peters et al (2000) showed that the size and location of the secondary flows are significantly affected by the interaction of labyrinth's leakage flow in turbines.…”
Section: Shrouded Tip Leakage Flow Interactionmentioning
confidence: 99%
“…Leakage flows from upstream cavities on engines generally emerge with lower momentum and less swirl than the mainstream flow, thus reducing the incidence at the inlet of the downstream blade row. The leakage flows may strengthen the endwall secondary flow on the downstream blade row (Anker & Mayer, 2002;Hunter & Manwaring, 2000;Paniagua et al, 2004;Pau et al, 2008). In addition, the ejection swirl angle can have a considerable effect to the efficiency of turbine stage, but the gain was restricted to the rotor due to a reduction in viscous dissipation and secondary losses (Ong et al, 2006).…”
Section: Coolant Injection and Rim Seal Flow Interactionsmentioning
confidence: 99%
“…As one can observe, the missing influence of the hub leakage flow leads to a decreased radial expansion of the distorted flow. The leakage flow results in negative incidence resulting in a separation of the flow near the wall and leads to a considerable amount of fluid which unites with passage and horseshoe vortex (Ghaffari and Willinger (2016), Anker and Mayer (2002) 14% relative span is covered with channel vortex flow which is in good agreement with Havakechian and Greim (1999) and Bohn et al (2006). Furthermore, due to the removal of the leakage flow the isentropic stage efficiency had been increased by another 0.95 percentage points, which stresses the influence of the interaction of leakage flow with the subsequent vane or blade and makes the appropriate design of the shroud's reentry geometry necessary.…”
Section: D Cfd Stage Simulationmentioning
confidence: 99%